PERAN PUSAT PELAYANAN TERPADU €ŽPEMBERDAYAAN €ŽPEREMPUAN DAN ANAK (P2TP2A) €ŽDALAM MENANGANI KASUS KDRT DI €ŽKOTA €ŽPROBOLINGGO - Slamet Hariyadi; Imanuddin Abil Fida (USRAH: Jurnal Hukum Keluarga Islam, 2021)
This study analyzes the active role of P2TP2A Probolinggo City in searching of €Žproblem solving of various domestic violence that occur in Probolinggo City. As €Žone of the government institutions formed through the mandate of the law, €ŽP2TP2A strives to carry out its main task, namely receiving reports of domestic €Žviolence cases and finding the best solution in solving them. The finding of the €Žanalysis is that the existence of P2TP2A is very much felt by the community. €ŽEvery year there are always problems that are reported and resolved through €Žmediation so as to maintain household harmony. In some cases, it continues to go €Žto court because the victim is adamant to use legal throught judge. €Ž